Role of Immunochromatographic Techniques in the Diagnosis of COVID-19 - Asif, Arham; Noman, Muhammad; Yasin, Hassan; Ahmad, Shaharyar; Naeem, Muhammad Tahir; Ijaz, Muhammad Saad; Naeem, Muhammad Abdullah; Riaz, Muhammad Waleed (Indus Journal of Bioscience Research, 2025)
The rapid and accurate diagnosis of SARS-CoV-2, the virus responsible for COVID-19, is crucial for controlling its spread and managing public health responses. SARS-CoV-2 is an airborne virus transmitted through direct contact or respiratory droplets from infected individuals. While some patients exhibit clear symptoms, others remain asymptomatic, making early detection essential to prevent further transmission. Diagnostic methods for SARS-CoV-2 primarily rely on two strategies: detecting viral RNA and identifying virus-specific antigens or antibodies. Viral RNA detection through reverse transcription polymerase chain reaction (RT-PCR) remains the gold standard for identifying active infections. In contrast, immunochromatographic techniques (ICT) offer a rapid and cost-effective alternative by detecting viral antigens or host antibodies. Immunological assays such as enzyme-linked immunosorbent assay (ELISA), chemiluminescent immunoassay (CLIA), and lateral flow immunoassay (LFIA) play a complementary role in identifying individuals with current or past infections. This review explores various molecular and serological methods for SARS-CoV-2 detection. RT-PCR offers high sensitivity and specificity, detecting viral RNA in respiratory samples, saliva, blood, urine, and stool within hours. However, it requires expensive equipment and trained personnel, with accuracy affected by sample quality and test kit efficiency. CRISPR-based detection provides high sensitivity and specificity, delivering results within an hour and integrating with lateral flow assays without the need for a thermocycler. Lateral flow assays enable rapid detection within 15 minutes by non-professionals but are limited by delayed antibody production. ELISA and CLIA are useful for immunity assessment, though ELISA lacks early detection capabilities, and CLIA is costly, limiting accessibility in economically challenged regions. Selecting an optimal method depends on available resources, accuracy, and the need for rapid diagnosis.